Teaching Children with Autism Abduction-Prevention Skills May Result in Overgeneralization of the Target Response. Issue 3 (May 2021) - Ledbetter-Cho, Katherine; Lang, Russell; Lee, Allyson; Murphy, Caitlin; Davenport, Katy; Kirkpatrick, Marie; Schollian, Melissa; Moore, Melissa; Billingsley, Glenna; O'Reilly, Mark
We replicated previous research using behavioral skills training (BST) to teach four children with autism to engage in a safety response following lures from civilian strangers. This study extends previous research by (a) employing abduction lures incorporating highly preferred tangible items; (b) assessing for maintenance and generalization across settings and caregivers; and (c) probing for overgeneralization of the safety response. A multiple baseline across participants design demonstrated target behavior acquisition and generalization to novel settings and caregivers. However, children who complied with directions from police officers during baseline emitted the safety response (e.g., running away) when approached by police officers following BST. Overgeneralization of the targeted safety response was corrected with discrimination training procedures. Maintenance of appropriate responses to civilians and officers was inconsistent and booster sessions were required for two participants. Results suggest practitioners should incorporate discrimination training and program for maintenance when teaching abduction-prevention skills to children with autism.